Homoseksual dalam Pandangan Kristen - Yohanes Yappo; Sandro Apriedo; Obertina Gomor; Sarmauli Sarmauli (Jurnal Silih Asah, 2025)
This article explores the issue of homosexuality from a Christian theological perspective by examining biblical teachings, traditions of the church, and contemporary theological discourse. Homosexuality has long been a controversial topic in Christianity because it is often associated with moral and doctrinal debates. This study aims to analyze how Christian theology interprets homosexual orientation and behavior, as well as how the church responds pastorally to individuals who identify as homosexual. Using a qualitative descriptive method with a literature review approach, this study reviews interpretations of biblical passages such as Genesis 19:1–29, Leviticus 18:22, Romans 1:26–27, and 1 Corinthians 6:9–10, which are frequently cited in discussions about homosexuality. The findings reveal that there are at least three dominant perspectives within Christianity: the conservative view, which rejects homosexual practice as sin; the moderate view, which distinguishes between homosexual orientation and action; and the liberal or progressive view, which accepts homosexuality as part of human diversity. The article concludes that the Christian view of homosexuality cannot be generalized and is influenced by historical, cultural, and denominational contexts. Therefore, a compassionate and dialogical pastoral approach is needed to uphold truth while welcoming all individuals with dignity.